2021
DOI: 10.1021/acs.cgd.0c01644
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonideal Shape Evolution during Potash Alum Crystallization Using Microcomputed Tomography and Three-Dimensional Image Analysis

Abstract: Nowadays, it is common to analyze crystallization processes and crystalline products using two-dimensional image analysis. Various techniques exist but they are not fundamentally capable of capturing the full morphology of particles due to their limitation in two dimensions. This is particularly true when complex shapes, e.g., through agglomeration or broken crystals, occur. Here, an approach is presented in which potash alum crystals are sampled from a laboratory-scale reactor at six time points over the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Figure D–F illustrates the growth of three seed crystals of our previous study . The crystal sizes were increased by factors of 1.78, 2.29, and 1.60, respectively, and the volumes were increased by factors 3.7, 3.9, and 3.5.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Figure D–F illustrates the growth of three seed crystals of our previous study . The crystal sizes were increased by factors of 1.78, 2.29, and 1.60, respectively, and the volumes were increased by factors 3.7, 3.9, and 3.5.…”
Section: Resultsmentioning
confidence: 86%
“…This mesh was smoothed by applying the function smoothpatch , three times (parameter itt = 3) to smoothen steps in the surface caused by discretization into voxels by μCT. Previously, we reported that this did not affect the volume or shape of similar crystals . For the overlaying procedure, the rotation and center point of the last μCT image served as reference.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations